Survey of the Presence of Nivalenol and Deoxynivalenol in Wheat Flour Factories of Khuzestan Province, Iran: presence of Nivalenol and Deoxynivalenol in wheat flour - Nazari Khorasgani, Zahra; Mahdavi, Mojtaba; Kalantari, Heibatullah; Goudarzi, Mehdi (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Background: Wheat is frequently contaminated by deoxynivalenol (DON) and nivalenol (NIV), which are type B trichothecenes produced by Fusarium fungi. Most problems related to these contaminants involve prolonged feed intake at low levels of contamination. This study investigated the occurrence of NIV and deoxynivalenol (DON) in wheat flour in flour factories in Khuzestan Providence, Iran. Methods: In total, 104 samples were collected in this study. An acetonitrile/water mixture (84:16, v/v) was used to extract the samples. The extracts were filtered and purified using a Whatman No. 4 paper and MycoSepTM 227 column. Then, they were evaporated to dryness at 40˚C under a nitrogen stream. After dissolving the dry residue in the mobile phase, containing a mixture of methanol, acetonitrile, and water (5:5:90, v/v/v), the contents of NIV and DON in the samples were measured in High-Performance Liquid Chromatography (HPLC) system with a column C18 (150 mm×4.6 mm ID, 5 µm) and a UV detector (220 nm). Results: The results showed that among 104 wheat flour samples, 28 (26.8%) and 54 (51.9%) samples were contaminated with NIV and DON, respectively. The mean and maximum concentrations were 118.75 and 2278 ng/g for NIV, and 593 and 67.88 ng/g for DON, respectively. Conclusion: Based on the findings, DON and NIV had significantly lower concentrations than the maximum tolerated level (1 µg/g), established by the Institute of Standards and Industrial Research of Iran. Therefore, there were no health risks for consumers at the studied contamination levels.